Trend of transplants and organ and tissue donations in Brazil: a time series analysis - Fernanda Gatez Trevisan dos Santos; Vanessa Aparecida Martim Mezzavila; Thamires Fernandes Cardoso da Silva Rodrigues; Luana Cristina Bellini Cardoso; Marcelo da Silva; Rosana Rosseto de Oliveira; Cremilde Aparecida Trindade Radovanovic
ABSTRACT Objectives: to indentify the time trend of rates of organs and tissues effective donors, of reports and types of transplanted organs per million people of the Brazilian population. Methods: ecological study, of time series, about reports of organ donations and on transplants. The data were provided by the Registro Brasileiro de Transplantes and analyzed using polynomial regression. Results an increasing trend was found for potential donors and effective donors, with an average increase of 2.33 and 0.92 per year, respectively. The South Region had the highest rate of potential donors (83.8) and effective donors (34.1) and the North Region, the lowest rate (20.2 and 3.9). The family refusal was the main obstacle to accomplish the donation. Conclusions the results show an increasing trend of potential donors and effective donors throughout Brazil, with emphasis on the southern region of the country. Among the main reasons for non-donation, it is worth emphasizing family refusal and medical contraindication prescription.